Molecular logic of neocortical projection neuron specification, development and diversity - Custo Greig, LF (2013)
The sophisticated circuitry of the neocortex is assembled from a diverse repertoire of neuronal subtypes generated during development under precise molecular regulation. In recent years, several key controls over the specification and differentiation of neocortical projection neurons have been identified. This work provides substantial insight into the “molecular logic” underlying cortical development, increasingly supporting a model in which individual progenitor-stage and postmitotic regulators are embedded within highly-interconnected networks that gate sequential developmental decisions. Here, we provide an integrative account of the molecular controls that direct the progressive development and delineation of subtype and area identity of neocortical projection neurons.